Transitional subjects : critical theory and object relations - Allen, Amy, 1970-; O'Connor, Brian, 1965- (New directions in critical theory., 2019)
"This project is the first of its kind. Carefully curated by the editors, themselves prominent critical theorists, these original commissioned essays open up new ground by bringing together leading psychoanalysts and critical theorists, many of whom are active in both fields. Authors, three of whom are affiliated with Columbia, include Axel Honneth, Joel Whitebrook, C. Fred Alford, Jessica Benjamin, Jon Mills, and Danielle Petherbridge. The book provides the definitive view of the significance of object-relations psychoanalysis for critical social theory today"--